2021
DOI: 10.1007/s00520-021-06306-6
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and lower health-related quality of life are associated with need for dietary support among colorectal cancer survivors with overweight or obesity

Abstract: Objective Two-third of colorectal cancer (CRC) survivors are overweight or obese. Psychological distress and low health-related quality of life (HRQoL) may be barriers to improving diet. We aimed to assess associations between psychological distress and HRQoL and the need for dietary support in CRC survivors with overweight or obesity. Methods All alive individuals diagnosed with CRC between 2000 and 2009, as registered by the Dutch population-based Eindho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…In our study, SCSs with a higher fear of cancer recurrence, anxiety, and depression were more likely to change their dietary intake in a healthier direction. This finding is compatible with a Duchy study of colorectal cancer survivors that found that those who experienced symptoms of anxiety or depression were more likely to express a need for dietary support than those who without such symptoms (27.6% and 28.7%, respectively) [ 54 ]. These findings suggest that the psychological difficulties of cancer survivors, including fear, anxiety, and depression, may serve as motivators for pursuing a healthier dietary intake.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, SCSs with a higher fear of cancer recurrence, anxiety, and depression were more likely to change their dietary intake in a healthier direction. This finding is compatible with a Duchy study of colorectal cancer survivors that found that those who experienced symptoms of anxiety or depression were more likely to express a need for dietary support than those who without such symptoms (27.6% and 28.7%, respectively) [ 54 ]. These findings suggest that the psychological difficulties of cancer survivors, including fear, anxiety, and depression, may serve as motivators for pursuing a healthier dietary intake.…”
Section: Discussionsupporting
confidence: 89%
“…27 Therefore, promotion of a healthier lifestyle needs to consider CRC survivors' psychological well-being, especially among those who are overweight or obese. 28 Because it has been shown that cancer survivors are more likely to make healthier lifestyle changes under the counsel and guidance of oncology care providers, 29 our results could reinforce the importance of tertiary prevention among CRC survivors postdiagnosis. Attention should also be given to better management of CRC survivors with comorbidities, because evidence suggests that lifestylerelated factors could help improve HRQoL for these individuals.…”
Section: Public Health Relevancementioning
confidence: 57%
“…A study in the United States found no significant relationship between BMI group and mental health-related quality of life in prostate cancer survivors [ 54 ]. Another study found significant psychological distress in overweight and obese cancer survivors who reported the need for dietary support [ 55 ]. A study among patients with cancer before receiving chemotherapy found a significant association between higher BMI scores and anxiety [ 56 ].…”
Section: Discussionmentioning
confidence: 99%